Metabolic reprogramming and lung cancer focused on roles, mechanism, and clinical prospects of circRNAs: a narrative review - Chen, Simin; Li, Mingxiao; Li, Siyao; Sun, Yinhui; Wang, Lihuai (Frontiers in Oncology, 2026)
Lung cancer remains one of the malignancies with the highest incidence and mortality rates worldwide, and its treatment continues to pose significant challenges. Metabolic reprogramming, as one of the hallmarks of cancer, supports the abnormal growth, proliferation, invasion, and drug resistance of cancer cells by altering glucose, lipid, and amino acid metabolic pathways, providing both energy and biosynthetic precursors. It has thus become a critical focus in lung cancer research. Circular RNAs (CircRNAs), owing to their unique closed-loop structure and high stability, play important roles in regulating tumor metabolism and progression. This review systematically summarizes the molecular mechanisms through which CircRNAs drive metabolic reprogramming in lung cancer, including the regulation of key metabolic enzymes, influence on metabolism-related signaling pathways, remodeling of the tumor microenvironment, and mediation of epigenetic modifications. Furthermore, CircRNAs demonstrate great potential in clinical applications for lung cancer, not only as biomarkers for early diagnosis and prognostic evaluation but also as promising therapeutic targets. Leveraging their stability and low immunogenicity, the development of CircRNA-based vaccines and targeted delivery systems has opened new avenues for lung cancer immunotherapy. However, challenges remain in the synthesis of CircRNAs, understanding their in vivo metabolism, and achieving multi-target synergistic interventions, which warrant further investigation. This review provides a theoretical foundation for in-depth exploration of the metabolic regulatory network in lung cancer and the development of precise therapeutic strategies, while also highlighting the broad prospects of CircRNAs in translational medicine. We conducted a literature search across databases including PubMed up to 2025, focusing on keywords related to circRNA, lung cancer, and metabolic reprogramming. Ultimately, 161 relevant references were included in this narrative review.